Menjadi Mukmin Sejati Prespektif Al-Qur’An: Telaah Tafsir Jalālain - Muzakky, Althaf Husein; Atieq, Muhammad Qoes; S, Jamaluddin (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2020)
The dynamics of Muslims are increasingly complex today. There are only some Muslims have adequate insights of religious knowledge. What is considered as a truth (absolute truth) relates to contestation of right opinions among them. The paper aims to describe the existence of good Muslims in the Qur'an based on the Jalālain interpretation or analysis which is very popular all over the world. A qualitative research using normative approach was done through the book interpretation of mauḍu'i and linguistics and sociohistorical with asbābun nuzūl  used in this study to find out the meaning of the Qur'anic verses about good Muslims. The results of this study showed that first, good Muslims are those who are balanced and proportional in the piety of spiritual and social faith. Second, there were many definitions of good Muslims in the Qur'an which need to be addressed wisely because they are provocative and debatable such as the words hijrah and jihad. Finally, the study also showed that most substantial meanings of being a good Mulim maintained ukhwah (brotherhood values) and harmony among people.